Pencegahan Penularan Multi-Resisten Organisme (MRO) Melalui Manset Tekanan Darah - Leli Ika Hariyati; Asroful Hulam Zamroni (Journal of Telenursing (JOTING), 2023)
This study aims to explore interventions to prevent the occurrence of multi-resistant organisms (MRO) in patients with blood pressure cuff placement in special care rooms. This research method uses the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines with the Scopus, PubMed, CINAHL, and SAGE databases. The results of the study found five types of interventions namely disinfection and decontamination with alcohol, addition of hydrogen peroxide in the sterilization process, cuff design with a barrier between the skin and the cuff, education and training programs for medical personnel, and development of standard procedure protocols. In conclusion, interventions to prevent the occurrence of multi-organism resistance in patients with blood pressure cuff placement do not only focus on equipment, but the knowledge and standard of cleaning procedures owned by health workers need to be improved and developed. Keywords: Blood Pressure Cuff, Prevention of Transmission, Multi-Organism Resistance (MRO)